"Not in (or Under) My Backyard": Geographic Proximity and Public Acceptance of Carbon Capture and Storage Facilities. Issue 3 (1st October 2013) - Krause, Rachel M.; Carley, Sanya R.; Warren, David C.; Rupp, John A.; Graham, John D.
<x xml:space="preserve">Abstract</x> Carbon capture and storage (CCS) is an innovative technical approach to mitigate the problem of climate change by capturing carbon dioxide emissions and injecting them underground for permanent geological storage. CCS has been perceived both positively, as an innovative approach to facilitate a more environmentally benign use of fossil fuels while also generating local economic benefits, and negatively, as a technology that prolongs the use of carbon‐intensive energy sources and burdens local communities with prohibitive costs and ecological and human health risks. This article extends existing research on the "not in my backyard" (NIMBY) phenomenon in a direction that explores the public acceptance of CCS. We utilize survey data collected from 1, 001 residents of the coal‐intensive U.S. state of Indiana. Over 80% of respondents express support for the general use of CCS technology. However, 20% of these initial supporters exhibit a NIMBY‐like reaction and switch to opposition as a CCS facility is proposed close to their communities. Respondents' worldviews, their beliefs about the local economic benefits that CCS will generate, and their concerns about its safety have the greatest impact on increasing or decreasing the acceptance of nearby facilities. These results lend valuable insights into the perceived risks associated with CCS technology and the possibilities for its public acceptance at both a national and local scale. They may be extended further to provide initial insights into likely public reactions to other technologies that share a similar underground dimension, such as hydraulic fracturing.